Effect of maternal Helicobacter Pylori infection on birth weight in an urban community in Uganda. Issue 1 (December 2016) - Wanyama, Ronald; Kagawa, Mike; Opio, Kenneth; Baingana, Rhona
Abstract Background Helicobacter pylori, a widespread infection particularly in developing countries has been associated with many adverse effects during pregnancy including hyperemesis gravidarum, neural tube defects in newborns, intrauterine fetal growth restriction and miscarriage. We sought to document the effects ofH. pylori infection on birth weight in a low-income setting in Kampala, Uganda. Methods This was a prospective cohort study conducted in Kampala between May 2012 and May 2013. The participants wereH. pylori positive andH. pylori negative HIV negative primigravidae and secundigravidae. Recruitment was at ≤18 gestation weeks and follow up assessments were carried out at 26 and 36 gestation weeks and soon after delivery.H. pylori infection was determined usingH. pylori stool antigen test. Maternal weight and height were measured, and body mass index (BMI) and gestational weight gain were calculated. Only term and live babies were considered. Low birth weight (LBW) was defined as a birth weight of <2500 gram. Results A total of 221 participants were enrolled with mean ± standard deviation (SD) age of 20.9 ± 2.7 years. The mean ± SD gestation age at delivery was 39.4 ± 1.0 weeks. Primigravidae were 61.5 % (n = 188) and 52.9 % (n = 117) of the participants were positive forH. pylori infection. Low pre-pregnancy BMI (<18.5 kg/m2 ) was recorded in 14.6 % (n = 28) while 38 % (n = 73) had a height <156 cm at recruitment. Of the infants born to the participants, 13.6 % (n = 26) had low birth weight (<2500 gram). Independent predictors for LBW were the mother being positive forH. pylori infection (odds ratio, OR, 3.6, 95 % CI 1.1 – 11.5;P = 0.031) maternal height at recruitment <156 cm (OR 3.4, 95 % CI 1.4–8.2;P = 0.008) and maternal weight gain rates <0.3 kg/week during the 2nd and 3rd trimesters (OR 3.8, 95 % CI 1.0–14.1;P = 0.044). Conclusion H. pylori infection is associated with LBW among primigravidae and secundigravidae in Kampala, Uganda.